The importance of being animate: Information selection as a function of dynamic human-environment interactions - Bailey, Rachel L.; Lang, Annie (Frontiers in Psychology, 2022)
This study examined whether the stability of highly relevant animate and inanimate information predicted encoding. Participants (N=149 young adults) viewed audiovisual media and completed a change detection task of screenshots taken from the viewing session. The screenshots were either left as originally viewed or a factor was altered. The factors were all motivationally (relevant to biological imperatives) and story (relevant to the ongoing narrative) relevant. Half were part of an animal and half were part of other environmental information. This was crossed with whether the information was stable or fleeting in the scene (e.g., a person’s clothing vs. their gestures). Changes to animals were more recognized than inanimate information. Changes to fleeting inanimate information were better recognized than changes to stable inanimate information. These findings indicate potential for relevant change in environmental threat and opportunity is adaptively significant and likely to increase attention and encoding across animate and inanimate categories of information.